Waste identification diagram and value stream mapping: A comparative analysis - Dinis-Carvalho, José (2019)
Purpose: The purpose of this paper is to compare the well-known value stream mapping (VSM) with a recent tool named waste identification diagram (WID), regarding the capacity of information representation and easiness of interpretation. Design/methodology/approach: The work begins with a brief literature review comparing the main tools for representation of production units, with special emphasis on VSM and WID, in terms of ability to identify several types of waste. Then, the authors developed the VSM and the WID of a specific production unit and after that several groups composed by students of Industrial Engineering (IE) and/or professionals from industry were asked to analyse/interpret only one of these diagrams. Finally, a questionnaire with closed and open questions was applied to the groups to evaluate the analysed tool. Findings: In general, the results revealed that WID is more effective than VSM and participants recognized that most of the WID elements are relevant. Specifically, a measure coined overall effectiveness was applied (based on the response time and percentage of correct interpretations), indicating a clear advantage of WID (22 per cent of correct interpretations per minute) compared to VSM (9 per cent of correct interpretations per minute). The main drawback pointed to the WID is the lack of representation of the information flow. Originality/value: This work contributes to the IE field by revealing WID as a new promising graphical tool for representation of production units, especially in terms of identification/quantification of wastes. The tool was quantitative and qualitatively evaluated by persons both from academia and industry.